1996
DOI: 10.1021/ma951392a
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Erucamide (13-cis-Docosenamide) in Isotactic Polypropylene

Abstract: Diffusion coefficients of erucamide (13-cis-docosenamide, H3C(CH2)11HCCH(CH2)7CONH2, eru) into isotactic polypropylene (i-PP) were determined under different isothermal conditions, viz., 323, 333, and 353 K in times of 15 days. Some other experiments were performed for several predetermined time intervals (5, 10, and 15 days) at a constant temperature (343 K). The diffusion cell which has been used to establish eru concentration profiles of diffusant within the polymer matrix is similar to that described and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 78 publications
1
38
0
Order By: Relevance
“…The activation energy of various solvents in PMMA ranged from 19 to 35 kcal/mol [145], and that of bis(2-ethylhexyl)phthalate in PVC was measured as 29 kcal/mol [146]. One example of activation energy for the molecular transport of middle-size molecules on the order of 337 g/mol was for instance 100 kJ/mol, determined for the diffusion of erucamide in isotactic polypropylene [147]. As far as the diffusion of polymers within polymers is concerned, an activation energy of 11.7 kcal/mol was found for the (PVC/poly(A-caprolactone))/system [148].…”
Section: -Determination Of the Activation Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The activation energy of various solvents in PMMA ranged from 19 to 35 kcal/mol [145], and that of bis(2-ethylhexyl)phthalate in PVC was measured as 29 kcal/mol [146]. One example of activation energy for the molecular transport of middle-size molecules on the order of 337 g/mol was for instance 100 kJ/mol, determined for the diffusion of erucamide in isotactic polypropylene [147]. As far as the diffusion of polymers within polymers is concerned, an activation energy of 11.7 kcal/mol was found for the (PVC/poly(A-caprolactone))/system [148].…”
Section: -Determination Of the Activation Energymentioning
confidence: 99%
“…Consequently, a two stage-diffusion process may be better in modelling this data. For example, two simultaneous Fickian processes, assuming a constant diffusion coefficient, were employed for the (erucamide/isotactic polypropylene) system above T g by Quijada-Garrido et al [147]. Furthremore, Dr. Hideko Oyama [144] showed using electron microprobe analysis (EMP), that for the (PVP/VER) bilayer films, the concentration profile could be divided into two parts.…”
Section: -Simultaneous Fickian Modelmentioning
confidence: 99%
“…The diffusion of small molecules in semicrystalline polymers occurs almost exclusively through the amorphous phase; for this reason the process has been considered classical Fickian as in a rubbery matrix [14][15][16][17][18][19] . However, there are some evidences suggesting the opposite in some special cases [20][21][22] . Diffusion is a function of structure of both the polymer and the diffusant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some diffusant molecules may be too large to enter the available amorphous interlayer separating two crystallites. The diffusion of eru in a semicrystalline matrix of i-PP was studied in 1996 by Quijada-Garrido et al 20) They showed that the diffusion of erucamide does not obey a classical Fickian model 23) and therefore it could not be accordingly explained by a simple diffusion mechanism. The nonFickian behaviour was justified by the complex morphology and texture of i-PP, the nature of the incompatible long-chain additive (eru), and its thermodynamic and hydrodynamic interactions [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…erucamide, diffusion in isotactic PP were found in the range emission detected during the 17 ns pulse at 105 K was probably generated as a result of photoexci-100-130 kJ mol 01 . 24 The very low activation energy found for T tation by Č erenkov radiation. 25 In PP film, contrary to the polyethylene system 4,6 no Py excimer õ T g in the case of PP is very similar to those estimated for polyethylene [5][6][7][8] ; hence, at temperaemission was detected for pulse irradiated samples.…”
mentioning
confidence: 99%